(untitled) (Research, Society and Development, 2022)
This article is the result of a qualitative research that aimed to identify and analyze the conceptions and socio-political and educational factors that characterize the multiserial school of EJA (Education of Youth and Adults) in the rural area of the municipality of Parnaíba (PI). The referred research was conducted in 2020, whose problem was methodologically addressed through documentary analysis, bibliographic research, content analysis, according to the perspective of Bardin (2011). As a conclusion we highlight that the multigrade rural school of EJA is a complex organization, highly challenging, with teaching structured in cycles, housing a plural public in terms of age, sex, gender, trajectories, dreams and expectations, levels of knowledge, inserted in a territory marked by social exclusion from public policies, without an adequate socioeconomic and pedagogical infrastructure, with committed educators, developing their activities without the appropriate conditions; The school cries out for support from the public authorities responsible for education in the municipality, for a review of its curricular structure, as well as for planning and evaluation tools, from conceptions to pedagogical practices.